(untitled) (Damascus University Journal for engineering sciences, 2023)
In this paper, we present a simulation of heat therapy for brain cancer using internal micro-sources, by studying a peripheral brain tumor model. Where a three-dimensional model of the tumor was built based on the medical images taken from an axial tomography device, and then these images were exported to a simulation program for thermal mapping during treatment, using two different energies of internal sources, 195000 W/m3 and 37900 W/m3 with different times for treatment application are 300s,600s,900s.. The study concluded that the treatment method used is highly effective in killing cancer cells while achieving a great safety ratio for healthy tissues, as treatment with internal heat sources is a promising treatment if micro-simulation is used and the energy sources and treatment time are controlled accurately.